Elements and machinery of non‐coding RNAs: toward their taxonomy. (14th April 2014) - Hirose, Tetsuro; Mishima, Yuichiro; Tomari, Yukihide
Abstract Although recent transcriptome analyses have uncovered numerous non‐coding RNAs (ncRNAs), their functions remain largely unknown. ncRNAs assemble with proteins and operate as ribonucleoprotein (RNP) machineries, formation of which is thought to be determined by specific fundamental elements embedded in the primary RNA transcripts. Knowledge about the relationships between RNA elements, RNP machinery, and molecular and physiological functions is critical for understanding the diverse roles of ncRNAs and may eventually allow their systematic classification or "taxonomy." In this review, we catalog and discuss representative small and long non‐coding RNA classes, focusing on their currently known (and unknown) RNA elements and RNP machineries.